Letter to the editor from the European Crop Protection Association (ECPA) Occupational and Bystander Exposure Expert Group (OBEEG) regarding a critical review of the role of Personal Protective Equipment (PPE) in agriculture. (November 2020) - Morgan, Neil; McEuen, Steven; Hewitt, Nicola J.; Durand-Réville, Julien
Highlights: ECPA- OBEEG responses to Garrigou et al., 2020 paper. Role of PPE for agricultural pesticide use. Several aspects of discussion require addressing. EFSA guidance is sufficiently precautionary. Redress balance of scientific interpretation. Abstract: We have addressed discussion points and conclusions from a review by Garrigou et al., 2020, entitled "Critical review of the role of PPE in the prevention of risks related to agricultural pesticide use", published in Safety Science (123, 104527). The paper takes an emotive stance and repeatedly refers to the "danger" involved in PPP use. Here, we focus on the implications of their discussions for the European regulatory system and put some of the observations they made into a more objective context. These include: calculation of AOELs; the type of personal protective equipment (PPE) discussed; default values for PPE protection factors; selection and interpretation of literature used to support claims; interpretation of the level of protection; and formulation effects. Their statement that PPPs " would be banned if it were not for this assumption of protection ", is overstated at best and misleading at worst. The claim that research suggests that under certain conditions, PPE is not protective enough could have important implications for safety assessments and authorisations of PPPs. Moreover, substantial research shows good performance for certified coveralls, as well as normal workwear. The most recent review of exposure data from multiple field studies regarding protection factors for a range of PPPs reveals that the EFSA guidance is sufficiently precautionary. We respectfully commend the amount of effort put into compiling the comprehensive review by Garrigou et al. but hope that a balanced opinion can be reached by taking our comments into account.